Using Artificial Intelligence in Managing Renewable Energy Projects in the Western Mountains (Gharyan, Jadu, and Nalut) - Abughalia, Jalal al-Mahdi; Farjani, Abdullah Younis al- (Libyan Journal of Contemporary Academic Studies, 2025)
This study aims to explore the potential of using artificial intelligence (AI) in managing renewable energy projects in the Western Mountains of Libya, specifically in Gharyan, Jadu, and Nalut. The research relied on a theoretical and environmental analysis of the three regions, a survey of expert opinions, and statistical analysis using tools such as SPSS and Python to develop prototypes that contribute to improving production and operational efficiency. The results demonstrated promising opportunities for adopting smart renewable energy in these regions, with the need to strengthen infrastructure and train local talent. The study also proposed a practical vision for establishing solar and wind power plants, as well as smart models for production forecasting and predictive maintenance. The study concludes with technical and regulatory recommendations to accelerate the implementation of these projects in line with the global transition to sustainable energy.
Keywords: Développement durable – Djebel Nefousa